Dissecting quasars with the J-PAS narrow-band photometric survey. Issue Volume 15:Issue S356(2019) (October 2019) - Bonoli, Silvia; Calderone, Giorgio; Abramo, Raul; Alcaniz, Jailson; Benitez, Narciso; Carneiro, Saulo; Cenarro, Javier; Cristóbal-Hornillos, David; Dupke, Renato; Ederoclite, Alessandro; San Juan, Carlos López; Marín-Franch, Antonio; et al.
Abstract: The J-PAS survey will soon start observing thousands of square degrees of the Northern Sky with its unique set of 56 narrow band filters covering the entire optical wavelength range, providing, effectively, a low resolution spectra for every object detected. Active galaxies and quasars, thanks to their strong emission lines, can be easily identified and characterized with J-PAS data. A variety of studies can be performed, from IFU-like analysis of local AGN, to clustering of high-z quasars. We also expect to be able to extract intrinsic physical quasar properties from the J-PAS pseudo-spectra, including continuum slope and emission line luminosities. Here we show the first attempts of using the QSFit software package to derive the properties for 22 quasars at 0.8 < z < 2 observed by the miniJPAS survey, the first deg 2 of J-PAS data obtained with an interim camera. Results are compared with the ones obtained by applying the same software to SDSS quasar spectra.